Magnon–phonon coupling and implications for charge-density wave states and superconductivity in cuprates - Struzhkin, Viktor V.; Chen, Xiao-Jia (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The mechanism of high-temperature superconductivity of copper oxides (cuprates) remains unsolved puzzle in condensed matter physics. The cuprates represent extremely complicated system, showing fascinating variety of quantum phenomena and rich phase diagram as a function of doping. In the suggested “superconducting glue” mechanisms, phonon and spin excitations are invoked most frequently, and it appears that only spin excitations cover the energy scale required to justify very high transition temperature Tc ~ 165 K (as in mercury-based triple layer cuprates compressed to 30 GPa). It appears that pres-sure is quite important variable helping to boost the Tc record by almost 30 degrees. Pressure may be also considered as a clean tuning parameter, helping to understand the underlying balance of various energy scales and ordered states in cuprates. In this paper, a review of mostly our work on cuprates under pressure will be given, with the emphasis on the interactions be-tween phonon and spin excitations. It appears that there is a strong coupling between superexchange interaction and stretching in-plane oxygen vibrations, which may give rise to a variety of complex phenomena, including the charge-density wave state intertwined with superconductivity and attracting a lot of interest recently.